Initial time value problem solutions for evolution inclusions with Sk type operators - Kasyanov, P.O.; Mel'nik, V.S.; Toscano, S. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2009)
For a large class of operator inclusions, including those generated by maps of Sk type, we obtain a general theorem on existence of solutions. We apply this result to some particular examples. This theorem is proved using the method of Faedo-Galerkin.